Toward a Simple Framework for Writing Histories of the Distributive Trades. (September 2016) - Sandgren, Fredrik
This article presents a simple analytic framework that can be used to write economic histories of the distributive trades where both retailing and wholesaling are systematically discussed. It is argued that a focus on the innovation of formats of distribution, in turn related to technological and organizational innovations and institutions, laws, rules and norms, is a fruitful approach when analyzing national histories of this economic sector and when making international comparisons. The framework is derived from previous historical studies, where a selection of ten major works is analyzed and discussed. The major strengths of the suggested framework are that it is firmly grounded in previous discussions, but also that it is simple, focused on important aspects, and adaptable to any place or any time.